UPAYA MENINGKAT MINAT BELAJAR DAN PRESTASI BELAJAR SISWADENGAN METODE TUTOR SEBAYA DAN LOMBA BERHADIAH - MIskam Miskam (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2022)
Islamic Religious Education Subjects are the main subjects that must be taught to students from Kindergarten to Higher Education. Judging from the material or scope, Islamic Religious Education broadly consists of 5 scopes, namely; the Qur'an and hadith, Aqedah, Morality, Fiqh and Dates and Islamic culture. Of the five spaces, not all of them are of interest to students. This is especially evident in the lack of feedback from students when the teacher finishes explaining or when the teacher gives students the opportunity to ask questions. In addition, when given questions, both daily test questions, mid-semester tests and semester tests. Of the five materials above, some are less attractive to students and the results are still low, including materials about the Qur'an, especially understanding of reading recitation and interpreting word for word from the verses of the Qur'an being studied. Before this research was conducted, when given questions about reading recitation and interpreting word for word/verse pieces, the average result only reached a maximum of 40%, moreover when it was assessed individually, it only reached 10%. However, after trying it with peer tutoring and prize competition methods, the results were very satisfying. The minimum average score achieved was at least 80%, even a few got a 100% score when viewed individually, and overall, the minimum score achieved was 85%. In addition, children's interest in learning, especially about material related to understanding or studying the verses of the Qur'an, increased more compared to before using this method. Moreover, students were very enthusiastic when an inter-group competition was held and as a reward to the winning group, prizes were given in the form of Scout SKU and scout pocket book.